Biomarkers of sustained systemic inflammation and microvascular dysfunction associated with post-COVID-19 condition symptoms at 24 months after SARS-CoV-2-infection - Jacobs, Lotte M. C.; Wintjens, Marieke S. J. N.; Nagy, Magdolna; Willems, Loes; ten Cate, Hugo; Spronk, Henri M. H.; van Kuijk, Sander M. J.; Ghossein-Doha, Chahinda; Netea, Mihai G.; Groh, Laszlo A.; van Petersen, André S.; Warlé, Michiel C. (Frontiers in Immunology, 2023)
Introduction Comprehensive studies investigating sustained hypercoagulability, endothelial function, and/or inflammation in relation to post-COVID-19 (PCC) symptoms with a prolonged follow-up are currently lacking. Therefore, the aim of this single-centre cohort study was to investigate serum biomarkers of coagulation activation, microvascular dysfunction, and inflammation in relation to persisting symptoms two years after acute COVID-19. Methods Patients diagnosed with acute SARS-CoV-2 infection between February and June 2020 were recruited. Outcome measures included the CORona Follow-Up (CORFU) questionnaire, which is based on an internationally developed and partially validated basic questionnaire on persistent PCC symptoms. Additionally, plasma biomarkers reflecting coagulation activation, endothelial dysfunction and systemic inflammation were measured. Results 167 individuals were approached of which 148 (89%) completed the CORFU questionnaire. At 24 months after acute infection, fatigue was the most prevalent PCC symptom (84.5%). Over 50% of the patients experienced symptoms related to breathing, cognition, sleep or mobility; 30.3% still experienced at least one severe or extreme (4 or 5 on a 5-point scale) PCC symptom. Multiple correlations were found between several PCC symptoms and markers of endothelial dysfunction (endothelin-1 and von Willebrand factor) and systemic inflammation (Interleukin-1 Receptor antagonist). No positive correlations were found between PCC symptoms and coagulation complexes. Discussion In conclusion, this study shows that at 24 months after acute COVID-19 infection patients experience a high prevalence of PCC symptoms which correlate with inflammatory cytokine IL-1Ra and markers of endothelial dysfunction, especially endothelin-1. Our data may provide a rationale for the selection of treatment strategies for further clinical studies. Trial registration This study was performed in collaboration with the CORona Follow-Up (CORFU) study (NCT05240742, https://clinicaltrials.gov/ct2/show/ NCT05240742).